Finding your roots. Season 3 [videorecording (DVD)] - Gates, Henry Louis, Jr; Gates, Henry Louis, Jr ([Publisher not identified], 2016)
Professor Gates' journey continues as a weekly series that will look at an ever-widening spectrum of our nation's fascinating ethnic mixture.